Dopamine-beta hydroxylase polymorphism and cocaine addiction - Guindalini, Camila (BioMed Central, 2008)
Cocaine addiction involves a number of medical, psychological and social problems. Understanding the genetic aetiology of this disorder will be essential for design of effective treatments. Dopamine-beta hydroxylase (DbH) catalyzes the conversion of dopamine to norepinephrine and could, therefore, have an influence on both cocaine action and the basal sensitivity of neurotransmitter systems to cocaine. Recently, the -1021C>T polymorphism have been found to strongly correlated with individual variation in plasma DbH activity. To test the influence of this polymorphism on the susceptibility of cocaine addiction, we decided to genotype it in a sample of 689 cocaine addicts and 832 healthy individuals. Genotypic and allelic analyses did not show any evidence of association with cocaine addiction, even after correcting for the effect of population stratification and other possible confounders. Our results do not support a major role of the -1021C>T polymorphism or the gene itself in the development of cocaine addiction but further examination of other variants within this gene will be necessary to completely rule out an effect.